Tumor treating fields and maintenance temozolomide for newly-diagnosed glioblastoma: a cost-effectiveness study. (3rd October 2019) - Guzauskas, Gregory F.; Pollom, Erqi L.; Stieber, Volker W.; Wang, Bruce C.M.; Garrison Jr, Louis P.
Abstract: Purpose: The EF-14 trial demonstrated that adding tumor treating fields (TTFields) to maintenance temozolomide (TMZ) significantly extends progression-free survival (PFS) and overall survival (OS) for newly-diagnosed glioblastoma (GBM) patients. This study assessed the cost-effectiveness of TTFields and TMZ for newly-diagnosed GBM from the US healthcare system perspective. Methods and materials: Outcomes for newly-diagnosed GBM patients were estimated over a lifetime horizon using an area under the curve model with three states: stable disease, progressive disease, or death. The survival model integrated the 5-year EF-14 trial results with long-term GBM epidemiology data and US background mortality rates. Adverse event rates were derived from the EF-14 trial data. Utility values to determine quality-adjusted life-years, adverse event costs, and supportive care costs were obtained from published literature. A 3% discount rate was applied to future costs and outcomes. One-way and probabilistic sensitivity analyses were performed to assess result uncertainty due to parameter variability. Results: Treatment with TTFields and TMZ was estimated to result in a mean increase in survival of 1.25 life years (95% credible range [CR] = 0.89–1.67) and 0.96 quality-adjusted life years (QALYs) (95% CR = 0.67–1.30) compared to treatment with TMZ alone. The incremental total cost was 188, 637 (95% CR = 145, 324–225, 330). The incremental cost-effectiveness ratio (ICER) was 150, 452 per life year gained and 197, 336 per QALY gained. The model was most sensitive to changes in the cost of TTFields treatment. Conclusions: Adding TTFields to maintenance TMZ resulted in a substantial increase in the estimated mean lifetime survival and quality-adjusted survival for newly-diagnosed GBM patients. Treatment with TTFields can be considered cost-effective within the reported range of willingness-to-pay thresholds in the US.